Fire resistance of oil palm shell lightweight aggregate concrete containing fly ash as partial cement replacement - Nadiah, Samsuddin (2019)
Oil palm shell (OPS) and fly ash are the waste products from Malaysia. They are disposed at the landfills in increasing quantity and this causes of environmental pollution. The steps taken to introduce these waste products disposed at the landfill. This thesis is present experimental study on the effect of elevated temperature on properties of oil palm shell (LWAC) containing fly ash as partial cement replacement. All the specimens were cured for 28 days. The temperature used is 100℃, 300℃, 500℃ and 800℃ for 1 hour. Two type of cooling system were used that is, air cooling and water cooling. This study shows that the compressive strength of concrete decrease as the temperature increase. The concrete losses more weight as temperature increase. Concrete containing fly ash as partial cement replacement weight and compressive strength increase compared to control specimen.